THE INFLUENCE OF WORK DISCIPLINE, WORKING ENVIRONMENT, ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT AND COMPENSATION ON SUPERMARKET EMPLOYEE PERFORMANCE ROXI ENDE - Se, Hyronimus; Langga, Lambertus (STIE Pelita Nusantara Semarang, 2023)
The purpose of this study was to determine the effect of work discipline, work environment, organizational culture, organizational commitment and compensation on the performance of Roxi Ende Supermarket employees. The population in this study were 50 Roxi Ende Supermarket employees. The sampling technique used the total sampling method or saturated sample with a total of 50 respondents. Data collection methods include observation, questionnaires, and documentation. The results of this study indicate that partially and simultaneously there is a significant influence between work discipline, work environment, organizational culture, organizational commitment and compensation on the performance of Roxi Ende Supermarket employees.